Les juifs d’Algérie face aux nationalités française et algérienne (1940-1963) - Pierre-Jean Le Foll Luciani (Revue des Mondes Musulmans et de la Méditerranée)
From the French conquest of Algeria in 1830 to the establishment of the independent Algerian state in 1962, the ones who conceived colonial, pro-Vichy, Zionist, or nationalistic definitions of French, Algerian and Israeli nationalities and citizenships thoroughly debated the rights that should be granted to the Jews in Algeria to such an extent that these same Jews had to face the legal, political, and cultural questions raised by these issues of nationality and citizenship. The thinking and attitudes of French legislators, European anti-Semites, and Algerian nationalists are quite well known. However, less in-depth research has been devoted to analyzing the various reactions of Jews to this issue. Their perception of French nationality has mainly been as assumed to be homogeneous. By focusing on turning points in the history of Algeria (Vichy, the Algerian war, and Independence), this essay aims at recovering how the persons who defined themselves as Jews contributed to shape competing definitions of nationalities. This essay also uses this specific case to reveal the tensions that arose around the issue of nationality in colonial and postcolonial Algeria.